Taraxasterol Inhibits LPS-Induced Inflammatory Response in BV2 Microglia Cells by Activating LXRα - Liu, Bin; He, Zhaoqi; Wang, Jingjing; Xin, Zhuoyuan; Wang, Jiaxin; Li, Fan; Fu, Yunhe (Frontiers in Pharmacology, 2018)
Taraxasterol, a pentacyclic-triterpene isolated from Taraxacum officinale, has been reported to have anti-inflammatory effects. In this study, we aimed to investigate the anti-inflammatory effects and mechanism of taraxasterol in LPS-stimulated BV2 microglia cells. BV2 microglia cells were treated with taraxasterol 12 h before LPS stimulation. The effects of taraxasterol on LPS-induced TNF-α and IL-1β production were detected by ELISA. The effects of taraxasterol on LXRα, ABCA1, TLR4, and NF-κB expression were detected by western blot analysis. The results showed that taraxasterol dose-dependently inhibited LPS-induced TNF-α and IL-1β production and NF-κB activation. Taraxasterol also disrupted the formation of lipid rafts and inhibited translocation of TLR4 into lipid rafts. Furthermore, taraxasterol was found to activate LXRα-ABCA1 signaling pathway which induces cholesterol efflux from cells. In addition, our results showed that the anti-inflammatory effect of taraxasterol was attenuated by transfection with LXRα siRNA. In conclusion, these results suggested that taraxasterol inhibits LPS-induced inflammatory response in BV2 microglia cells by activating LXRα-ABCA1 signaling pathway.